TINJAUAN KRITIS ATAS PUTUSAN PANEL WTO DALAM SENGKETA EU-INDONESIA TENTANG MINYAK SAWIT DAN BIOFUEL (DS593/DS600) SERTA IMPLIKASINYA BAGI HUKUM PERDAGANGAN MULTILATERAL - Ahmad Fahrul Rozi; Annie Myranika; Ani Wahyuni; Regina Yura Fitriah Sari; Oky Rona Wijaya (CV. Lafadz Jaya, 2026)
This article analyses the WTO Panel’s ruling in the dispute European Union – Certain Measures Concerning Palm Oil and Oil Palm Crop-Based Biofuels (DS593/DS600) involving Indonesia, Malaysia and the European Union. The ruling, issued in January 2025, confirms the compatibility of the RED II legal framework with WTO rules, but identifies inconsistencies in the implementation of the Delegated Act regarding the classification of high-risk indirect land-use change (ILUC). This article examines the legal implications of the ruling regarding the principle of non-discrimination under the Agreement on Technical Barriers to Trade (TBT Agreement), the balance between climate policy and trade obligations, and the dynamics of WTO dispute settlement system reform following MC13. The analysis employs a normative-comparative legal research method based on official WTO documents and the latest literature on international trade law. The research findings indicate that the Panel’s ruling establishes an important precedent regarding the limits on the legitimacy of unilateral actions based on environmental concerns within the multilateral framework, whilst also underscoring the urgency of Appellate Body reform to maintain the effectiveness of the WTO dispute settlement system.